2015
DOI: 10.1016/j.icarus.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Yarkovsky-driven spreading of the Eureka family of Mars Trojans

Abstract: Out of nine known stable Mars Trojans, seven appear to be members of an orbital grouping including the largest Trojan, Eureka. In order to test if this could be a genetic family, we simulated the long term evolution of a tight orbital cluster centered on Eureka. We explored two cases: cluster dispersal through planetary gravity alone over 1 Gyr, and a 1 Gyr evolution due to both gravity and the Yarkovsky effect. We find that the dispersal of the cluster in eccentricity is primarily due to dynamical chaos, whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Di Sisto, Ramos & Beaugé 2014;Wong, Brown & Emery 2014), Mars (see e.g. Marzari et al 2002;Connors et al 2005;Scholl, Marzari & Tricarico 2005;Ćuk, Christou & Hamilton 2015) or Neptune (see e.g. Parker 2015;Gerdes et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Di Sisto, Ramos & Beaugé 2014;Wong, Brown & Emery 2014), Mars (see e.g. Marzari et al 2002;Connors et al 2005;Scholl, Marzari & Tricarico 2005;Ćuk, Christou & Hamilton 2015) or Neptune (see e.g. Parker 2015;Gerdes et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These amplitudes are relatively immune to change by the Yarkovsky effect ( Ćuk et al, 2015) and a good proxy for the original orbits of the family members. For the Eureka family, the spread in amplitudes translates into a velocity spread of < 3 m s −1 ( Ćuk et al, 2015;, comparable to the escape velocity from Eureka (∼ 1 m s −1 for a bulk density ρ = 1 − 3 g cm −3 ). This implies a gentle separation from the primary which is consistent with the YORP fission and escape scenario but more difficult to reconcile with an impact origin.…”
mentioning
confidence: 95%
“…The sample distribution moments are, however, very similar; the respective means and standard deviations are 2.95 ± 0.58 m s −1 and 2.79 ± 0.50 m s −1 . Therefore, this procedure may also be thought of as alternative method to calculate Trojan libration amplitudes (Milani, 1993;Ćuk et al, 2015) and we can use the new estimates to test the correlation found by Ćuk et al with the mean orbital inclinations. We find, as those authors did, that the two are negatively correlated but more weakly so (R 2 =0.17 vs 0.83 for that first set of libration amplitudes).…”
Section: Use Of the Formal Variancementioning
confidence: 99%